A phase 1b open‐label study of sodium selenate as a disease‐modifying treatment for possible behavioral variant frontotemporal dementia. Issue 1 (5th May 2022) - Vivash, Lucy; Malpas, Charles B.; Meletis, Christian; Gollant, Meghan; Eratne, Dhamidhu; Li, Qiao‐Xin; McDonald, Stuart; O'Brien, William T.; Brodtmann, Amy; Darby, David; Kyndt, Christopher; Walterfang, Mark; et al.
Abstract: Introduction: Sodium selenate increases tau dephosphorylation through protein phosphatase 2 activation. Here we report an open‐label Phase 1b study of sodium selenate as a disease‐modifying treatment for behavioral variant frontotemporal dementia (bvFTD). Methods: Twelve participants with bvFTD received sodium selenate (15 mg, three times a day) for 52 weeks. Safety assessments were carried out throughout the trial. Primary outcomes were frequency of adverse events (AEs), serious adverse events (SAEs), and discontinuations. Secondary outcomes of potential efficacy included cognitive and behavioral assessments, magnetic resonance imaging (MRI) whole brain volume, and cerebrospinal fluid (CSF) and blood total tau (t‐tau), phosphorylated tau (p‐tau), and neurofilament light (NfL) levels, which were measured at baseline and at week 52. Results: Sodium selenate was safe and well tolerated. All participants completed the study, and the majority (64.7%) of reported AEs were mild. One SAE occurred, which was not treatment related. Small declines in MRI and cognitive and behavioral measures were observed over the treatment period. There was no evidence for change in CSF protein levels (t‐tau, p‐tau, or NfL). Further analysis showed two distinct groups when measuring disease progression markers over the course of the study—one (n = 4) with substantial brain atrophy (2.5% to 6.5% reduction) and cognitive and behavioral decline over the 12‐month treatment period, and the second group (n = 7) with no detectable change in cognitive and behavioral measures and less brain atrophy (0.3% to 1.7% reduction). Conclusion: Sodium selenate is safe and well tolerated in patients with bvFTD. Randomized‐controlled trials are warranted to investigate potential efficacy.